Oxytocin induced labor causes region and sex‐specific transient oligodendrocyte cell death in neonatal mouse brain. Issue 1 (19th November 2019) - Hirayama, Takashi; Hiraoka, Yuichi; Kitamura, Eri; Miyazaki, Shinji; Horie, Kengo; Fukuda, Tomokazu; Hidema, Shizu; Koike, Masato; Itakura, Atsuo; Takeda, Satoru; Nishimori, Katsuhiko
Abstract: Aim: Previous reports showed associations between oxytocin induced labor and mental disorders in offspring. However, those reports are restricted in epidemiological analyses and its mechanism remains unclear. In this study, we hypothesized that induced labor directly causes brain damage in newborns and results in the development of mental disorders. Therefore we aimed to investigate this hypothesis with animal model. Methods: The animal model of induced labor was established by subcutaneous oxytocin administration to term‐pregnant C57BL/6J mice. We investigated the neonatal brain damage with evaluating immediate early gene expression ( c‐Fos, c‐Jun and JunB ) by quantitative polymerase reaction and TdT‐mediated dUTP nick end labeling staining. To investigate the injured brain cell types, we performed double‐immunostaining with TdT‐mediated dUTP nick end labeling staining and each brain component specific protein, such as Oligo2, NeuN, GFAP and Iba1. Results: Brain damage during induced labor led to cell death in specific brain regions, which are implicated in mental disorders, in only male offspring at P0. Furthermore, oligodendrocyte precursors were selectively vulnerable compared to the other cell types. This oligodendrocyte‐specific impairment during the perinatal period led to an increased numbers of Olig2‐positive cells at P5. Expression levels of oxytocin and Oxtr in the fetal brain were not affected by the oxytocin administered to mothers during induced labor. Conclusion: Oligodendrocyte cell death in specific brain regions, which was unrelated to the oxytocin itself, was caused by induced labor in only male offspring. This may be an underlying mechanism explaining the human epidemiological data suggesting an association between induced labor and mental disorders.